KEBIJAKAN PENGEMBANGAN TERNAK SAPI POTONG DI WILAYAH SENTRA PRODUKSI BERBASIS TANAMAN PANGAN DI INDONESIA - CHAIRUL MUSLIM; TJETJEP NURASA (SOCA: Jurnal Sosial Ekonomi Pertanian, 2006)
Integrated Rice-Livestock System (SIPT) Program is a part of Agribusiness-BasedLivestock Development Program. Meanwhile, the location of SIPT is a part of IntegratedCrops Management implementation. SIPT was initially implemented in 2002 covered 11provinces. Currently, the program covers one province as a central producing area of beefcattle. The program is mainly purposed to optimize local resources utilization such as hayfor livestock feed and processed cow dung (manure) for improving crops fertility (zerowaste). The core performance of SIPT is an effort of beef cattle production development asan alternative breakthrough program that can be expected to fulfill the challenge andrequirement of the adequate beef cattle development (self-sufficiency) in 2005. Hence, thisarticle aims to analyze government’s programs of beef cattle in Indonesia, particularlyrelated to SIPT Program. Apart from that, the article also reviews some research result ofbeef cattle development, especially in primary commodity area. .